The invention and gendering of Epicurus - Gordon, Pamela, 1957- (The University of Michigan Press, 2012)
The school of Greek philosopher Epicurus, which became known as the Garden, famously put great stock in happiness and pleasure. As a philosophical community, and a way of seeing the world, Epicureanism had a centuries-long life in Athens and Rome, as well as across the Mediterranean. The Invention and Gendering of Epicurus studies how the Garden's outlook on pleasure captured Greek and Roman imaginations--particularly among non-Epicureans--for generations after its legendary founding. Unsympathetic sources from disparate eras generally focus not on historic personages but on the symbolic Epicurean. And yet the traditions of this imagined Garden, with its disreputable women and unmanly men, give us intermittent glimpses of historical Epicureans and their conceptions of the Epicurean life. Pamela Gordon suggests how a close hearing and contextualization of anti-Epicurean discourse leads us to a better understanding of the cultural history of Epicureanism. Her primary focus is on sources hostile to the Garden, but her Epicurean-friendly perspective is apparent throughout. Her engagement with ancient anti-Epicurean texts makes more palpable their impact on modern responses to the Garden. Intended both for students and for scholars of Epicureanism and its response, the volume is organized primarily according to the themes common among Epicurus' detractors. It considers the place of women in Epicurean circles, as well as the role of Epicurean philosophy in Homer and other writers.